La Perception Du Risque Routier. Le Cas De La Conduite Des Conducteurs Professionnels De Transport En Commun A Abidjan - Roger, Tieffi Hassan Guy; Bruno, Kanga Kouakou; Narcisse, Achi EssÃ©tchi (European Scientific Journal, ESJ, 2017)
This study examines the perception of the risk of accidents related to the driving activity of the Public Transport Professional Drivers (CPTC) in Abidjan. 186 CPTC of Abidjan, whose age varies between 18 and 50 years, and who holds a different driving license are investigated. Their perception of risk is measured from a questionnaire consisting of 37 items on a 5-point scale. The results indicate that there are as many CPTCs that perceive the least risk of driving-related accidents as those who perceive it the most. They also show that the age and duration of driving licenses influence the perception of the risk of CPTC accidents.